Youth-focused citizen science: Examining the role of environmental science learning and agency for conservation. (April 2017) - Ballard, Heidi L.; Dixon, Colin G.H.; Harris, Emily M.
Abstract: Citizen science by youth is rapidly expanding, but very little research has addressed the ways programs meet the dual goals of rigorous conservation science and environmental science education. We examined case studies of youth-focused community and citizen science (CCS) and analyzed the learning processes and outcomes, and stewardship activities for youth, as well as contributions to site and species management, each as conservation outcomes. Examining two programs (one coastal and one water quality monitoring) across multiple sites in the San Francisco Bay Area, CA, in- and out-of-school settings, we qualitatively analyzed in-depth observations and pre- and post-program interviews with youth and educators. First, we examined evidence from the programs' impacts on conservation in the form of contribution to site and species management. We found that youth work informed regional resource management and local habitat improvement. Second, we examined the youth participants' environmental science agency (ESA). ESA combines not only understanding of environmental science and inquiry practices, but also the youths' identification with those practices and their developing belief that the ecosystem is something on which they act. We found that youth developed different aspects of environmental science agency in each context. We identify three key CCS processes through which many of the youth developed ESA: ensuring rigorous data collection, disseminating scientific findings to authentic external audiences, and investigating complex social-ecological systems. Our findings suggest that when CCS programs for youth support these processes, they can foster youth participation in current conservation actions, and build their capacity for future conservation actions. Highlights: We examined two youth-focused community and citizen science (CCS) programs. We develop and apply "environmental science agency" to link conservation learning and action. Youth CCS contributed data to coastal area management and stream restoration. Youth developed ecological knowledge, expertise, and capacity to take action. CCS should help youth take responsibility for rigorous data and sharing results.